Normolipemic xanthomatized Sweet's syndrome: A variant of Sweet's syndrome with myelodysplastic syndrome. Issue 5 (13th February 2021) - Kamimura, Anna; Yanagisawa, Hiroto; Tsunemi, Yuichiro; Kusano, Takeru; Arai, Eiichi; Tsuchida, Tetsuya; Nakamura, Koichiro
Abstract: We report a rare case of xanthomatized Sweet's syndrome with myelodysplastic syndrome (MDS) in a patient who presented with erythematous plaques on his chest that were elevated and became yellowish. A diagnosis of MDS with single lineage dysplasia was made during the development of the eruption. Bone marrow biopsy showed an increased number of megakaryoblasts. Histopathologically, there was neutrophil infiltration with leukocytoclasia and the infiltration of xanthomatous cells. Immunohistochemical analysis revealed that the xanthomatized cells were predominantly CD163 positive. We propose that our case of xanthomatized neutrophilic dermatosis is a rare clinicopathological variant of Sweet's syndrome associated with a hematologic disorder.